2016
DOI: 10.1016/j.eplepsyres.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam and clonazepam use in epilepsy: Results from a UK database incident user cohort study

Abstract: Among adult and pediatric patients in the UK, CLB is more often prescribed for epilepsy than CZP. The median CLB dosage used by both adults and children remained stable over the 16-year study period, while the median CZP dosage increased in both adults and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…Adverse events profile of these drugs might have also affected the rate of treatment discontinuation and switch. Treatment patterns in LGS patients have not been extensively evaluated; although in the UK study noted above, treatment duration differed from that reported in the current study [15]. The median treatment duration was similar between the epilepsy patients treated with clobazam or clonazepam.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Adverse events profile of these drugs might have also affected the rate of treatment discontinuation and switch. Treatment patterns in LGS patients have not been extensively evaluated; although in the UK study noted above, treatment duration differed from that reported in the current study [15]. The median treatment duration was similar between the epilepsy patients treated with clobazam or clonazepam.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar findings were observed in a database study conducted in adult epilepsy patients in the United Kingdom (UK). In that study, prior to treatment initiation, patients initiating clobazam treatment were younger and had greater use of concomitant AEDs than those receiving clonazepam [15]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, a comparison of real-world use of clobazam and clonazepam in patients with epilepsy in the United Kingdom showed that median clonazepam dosages increased by 25% and 50% for adults and children, respectively, while median clobazam dosages did not change from baseline to the last follow-up (adults, 5.2–5.5 years; children, 5.5–6.3 years). 26 It is also important to note that clobazam is structurally different from classic benzodiazepines: the 2 nitrogen components at the core of all benzodiazepines have a 1,5 configuration in clobazam compared to a 1,4 configuration in the classic benzodiazepines (e.g., diazepam, lorazepam, and clonazepam). Clobazam and its active N -desmethyl metabolite also appear to display significantly greater binding affinity to the α2 vs α1 subunit of the GABA-A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been employed in other similar CPRD studies using these two variables. 77,78 Random samples of 50,000 patients from these limited samples were then taken to form the five main analysis samples (Table 12). Product codes (CPRD unique code for treatment selected by the GP) associated with relevant prescriptions used in the treatment of five case study conditions were used to select the patients to be included in the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate methods to impute these variables are, however, limited, and our approach was similar to other studies using CPRD data. 77,78 Third, the identification of patients within CPRD with the five case study conditions (see Table 11) was based solely on product codes, rather than on a specific medical diagnosis (identified using Read codes in CPRD). This was straightforward for four of the five conditions, but required additional assumptions for the secondary prevention of myocardial infarction cohort.…”
Section: Limitations Of the Cost Analysismentioning
confidence: 99%